Study of Growth Curve of Lactobacillus plantarum FNCC 0026 and Its Antibacterial Activity - Safarini Marwah; Achmad Toto Poernomo; Esti Hendradi (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Lactobacillus plantarum is one of the lactic acid bacteria (LAB) with strong antibacterial activity. However, these bacteria show different growth for each strain. The turbidimetric bacterial growth curve approach is the most accurate, fastest, and most reproducible method for obtaining an overview of the bacterial life cycle. In addition, we also examined the antibacterial activity of each observation of the growth curve. Objective: The aim of the study was to determine the optimal incubation time with the highest biomass concentration and antibacterial activity of the Lactobacillus plantarum FNCC 0026. Method: Observations of optical density (OD) values "‹"‹were performed simultaneously on 10 points of Lactobacillus plantarum FNCC 0026 and performed every 12 hours. Antibacterial activity tested against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 8739. Result: The Lactobacillus plantarum FNCC 0026 fermentation broth showed the highest OD value and antibacterial activity after 30 hours of incubation. The maximum diameter of the inhibition zone against Staphylococcus aureus ATCC 25923 and Escherichia coli 25923 were 17.08 ± 0.51 mm and 16.83 ± 0.54 mm. Conclusion: The results showed that the antibacterial activity had a linear relationship with the concentration of bacteria. In the Lactobacillus plantarum FNCC 0026, the optimum cultivation time is in the lag phase (24 – 30 hours).